Comparison of Conventional and Modern Wound Care in Post-Section Wounds at Cut Mutia Hospital, North Aceh Regency in 2023 - Yusnidaryani, Yusnidaryani; Taufiq, Said; Fauzi, M. Jamil (Syntax Corporation Indonesia, 2024)
The World Health Organization (WHO) sets the average cesarean sections (CS) standard at 5-15% per 1000 births. However, cesarean section rates in private hospitals exceed 30%, compared to 11% in government hospitals. This study investigates the prevalence and complications of surgical wound infections post-cesarean section and the effectiveness of modern wound dressing techniques in reducing these infections. Data analysis reveals cesarean wound infections occur during hospitalization (27%), re-admission (1%), and post-discharge (71%). Surgical wound infections (SWI) significantly increase morbidity, treatment duration, and healthcare costs, with a direct death rate ranging from 3% to 75% globally. The study evaluated modern wound dressings adhering to